Benefits of proper practice method to a good tone production of double bass / Mohd Rasyid Mohd Pozi - Mohd Pozi, Mohd Rasyid (2012)
This study was conduct to explore benefits of proper practice method of double bass towards the good tone production. The purpose of this studies to identify most suitable method or playing position and gives some useful guide and skills for double bassist to be trained in the exact practice method of right hand and left hand to produce a good tone on double bass. For this particular study, there are two collection method of data. Primary data collection, which include the interviews such as telephone, questionnaire that are either personally administered or send through mail. Secondary data for this research is done through journals, articles, literature review, documents which were related to the study. From the findings, it shows that when double bassist executes a proper method and techniques In double bass playing, it will produce a beneficial results for the double bassist. All the method and techniques that have been discussed will lead a young double bassist a steps to deliver a quality performance.